Sitotoksisitas bahan restorasi cyanoacrylate pada variasi perbandingan powder dan liquid menggunakan MTT assay (Cytotoxicity of the cyanoacrylate restoration material with variation of powder and liquid ratio by using MTT assay) - Asti Meizarini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The requirements for dental material include not toxic, not irritant, no carcinogenic potential, nor cause an allergic response with the use in oral cavity. The cyanoacrylate restoration material has certain substance that can be toxic. Because of the ratio amount of powder and liquid is not known, it can lead the restoration more toxic. The purpose of this study was to know the cytotoxicity of the cyanoacrylate restoration material with different variation of powder and liquid ratio using MTT assay. Six cylinder samples of 5 mm in diameter and 2 mm in thickness were used for each group of 1:1.00; 1:0.75; 1:0.50 powder and liquid ratio of cyanoacrylate restoration materials. Each of samples was immersed in eppendorf micro tubes consisting of media culture. After 24 hour, the immersion of media culture was used to investigate the cytotoxic effect to BHK-21 cell lines by MTT assay method. The density of optic formazan indicated the amount of living cells. All data were statistically analyzed by one-way ANOVA and HSD. The results showed that the percentage of living cells amount of powder and liquid ratio 1:1.00; 1:0.75; 1:0.50 were 98.59%; 95.76%; 94.92% respectively. There was a significant difference between 1:1.00 and 1:0.50 group ratio. The conclusion was that the cytotoxicity between 1:1.00 and 1:0.50 powder and liquid ratio of cyanoacrylate restoration materials in this study decreased.